LICAVAL: combination therapy in acute and maintenance treatment of bipolar disorder - Demétrio Frederico N (Trials, 2010)
Abstract Background The challenge of Bipolar Disorder (BD) treatment is due to the complexity of the disease. Current guidelines represent an effort to help clinicians in their everyday practice but still have limitations, specially concerning to long term treatment. LICAVAL (efficacy and tolerability of the combination of LIthium and CArbamazepine compared to lithium and VALproic acid in the treatment of young bipolar patients) study aim to evaluate acute and maintenance phase of BD treatment with two combined drugs. Methods LICAVAL is a single site, parallel group, randomized, outcome assessor blinded trial. BD I patients according to the DSM-IV-TR, in depressive, manic,/hypomanic or mixed episode, aged 18 to 35 years are eligible. After the diagnostic assessments, the patients are allocated for one of the groups of treatment (lithium + valproic acid or lithium + carbamazepine). Patients will be followed up for 8 weeks in phase I (acute treatment), 6 months in phase II (continuation treatment) and 12 months in phase III (maintenance treatment). Outcome assessors are blind to the treatment. The main outcome is the evaluation of changes in mean scores on CGI-BP-M between baseline and endpoint at the end of each phase of the study. Results LICAVAL is currently in progress, with patients in phase I, II or III. It will extended until august 2012. Conclusions Trials comparing specific treatments efficacy in BD (head to head) can show relevant information in clinical practice. Long term treatment is an issue of great important and should be evaluated carefully in more studies as long as BD is a chronic disease. Trial registration ClinicalTrials.gov Identifier: NCT00976794